2015_PHD_VERHELST_EEL - Acoustic telemetry data for European eel (Anguilla anguilla) in the Scheldt estuary and southern North Sea (Belgium) ... - Verhelst, Pieterjan; Reubens, Jan; Coeck, Johan; De Maerteleire, Nico; Desmet, Peter; Gelaude, Emilie; Mouton, Ans; Pieters, Sébastien; Reyserhove, Lien; Robberechts, Karen; Moens, Tom (Marine Data Archive, 2020)
This is an acoustic telemetry dataset published by Ghent University. It contains animal (fish) tracking data collected by the Permanent Belgian Acoustic Receiver Network (https://lifewatch.be/en/fish-acoustic-receiver-network) for the project/study 2015_phd_verhelst_eel, using VEMCO tags (V13) and receivers (VR2AR, VR2Tx, VR2W). In total 136 female individuals of European eel (Anguilla anguilla) were captured, tagged and released between 2015 and 2018 in the Scheldt estuary, to study their migration behaviour - especially their use of selective tidal stream transport - in a tidal system without migration barriers. ... : Large estuaries with a complete salinity gradient from a tidal freshwater zone to marine have become rare due to water regulating constructions such as sluices, shipping locks, water pumping stations and dams. However, the Scheldt estuary in Belgium still has an extensive estuary of ca 160 km. Diadromous fish have to overcome substantial distances which come with a high energetic cost. Due to the high energetic cost of migration and the low adult survival, some of these species have developed semelparity. Consequently, a bioenergetic trade-off between migration and reproduction may exist for semelparous fish species, especially since many will stop feeding during migration: the smaller the energy expenditure during migration, the larger the amount of energy that may remain available for gonad maturation. An example where migration can have important bioenergetic repercussions is migration through strong tidal systems. To reduce energy loss in such systems, fish may perform selective tidal stream transport ...